Prevalence of SARS-COV-2 Antibodies in Dental Healthcare Providers - Shawana Iqbal, Shahab Adil, Najeeb-Ul-Haq, Mohsina Haq, Kawish Syed, Naila Sumbal, Madiha Ishfaq, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Occupational hazards and risks are a common public health issue, especially when healthcare workers safety is concerned; they are on high risk of catching infections such like COVID-19. The possibility of cross-infection between dental practitioners and patients is significantly higher due to the close exposure of dental staff to patient oral environment. Aim: To assess the prevalence of SARS-COV-2 antibodies in dental workers working in the Peshawar Dental College and Hospital, Peshawar. Study Design: Cross sectional study Place and Duration of Study: Department of Orthodontics, Peshawar Dental College & Hospital, Peshawar from 1st January 2020 to 31st December 2020. Methodology: One hundred and thirty three dental workers were enrolled. The investigation was run to detect immunoglobulin G and M antibodies against the SARS-CoV-2-2. The aspirated aerosol and air was evacuated and dissipated into the atmosphere. Results: Mean age was 29.4±1.4 years and males were dominant 74 (55.6%) and male workers found greater with positive antibodies. The prevalence of SARS-CoV-2 antibodies was 33.0%. Proportionately dental assistants (20.5% vs 16.9%) and ancillary staff (20.5% vs 10.1%) had higher prevalence. Sore throat and body aches were more common in positive antibodies cases while travel history was found significantly associated with it (40.9% vs 25.0%, p-value, 0.05). Conclusion: High frequency of SARS-COV-2 antibodies was found in dental workers showing a high infection rate of COVID-19 in healthcare workers in local settings. Keywords: Dental workers, COVID-19 infection, Antibodies, SARS-COV-2